Preferensi Pengunjung Terhadap Daya Tarik Objek Wisata Teluk Palu di Kota Palu - Rizkhi, Rizkhi; Buchori, Imam (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
This research aiming to find out the motivation of tourist to visiting attractions of Teluk Palu in Palu City. The approach used in this research is quantitative, by using data processing methods is frequency distribution for grouping categories according to needs variables and descriptive exploratory analysis for exposure image of the phenomenon in this case to find out the aspects that can direct visitors to a tourist destination. Preferences of visitors against the Teluk Palu tourist attraction arise from various aspects, ranging from a wide variation of tourist attractions on offer, the vitality of a tourist area, easy accessibility and affordability of distance and cost by visitors so that they are motivated and love to do tourism activities in the Gulf region of Palu. In addition, associated with fondness or option of tourist attraction that favored as well as the assessment of the quality of the visitor attraction Teluk Palu. There are huge expectations from visitors to the progress and development of the tourist areas, as well as a requirement that must be fulfilled, so the involvement of government, community, and other tourism stakeholders is needed in the planning, development and proper management of aspects that support the Teluk Palu tourism activities.